YAM PRODUCTION AS PILLAR OF FOOD SECURITY IN LOGO LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA - Nahanga Verter; Vera Becvarova (European Scientific Journal, ESJ, 2014)
Food production is a necessary condition in reducing hunger and ensuring food security, especially to the poor rural dwellers that are vulnerable to misfortune. This contribution is an attempt to explore the importance of yam production, socioeconomic characteristics of farmers, constraints to yam production, and yam as an integral of food security in the Logo Local Government of Benue State, Nigeria. The primary data for the study were collected from the I40 yam farmers who were randomly selected with a structured questionnaire. The data are mostly analysed with frequency and percentage. The findings of the study show that the majority of the respondents are males. The main reasons for yam farm as indicated by the respondents were food security, income and employment. The major constraints to yam production as reported by the respondents were lack of fertilizer, access to finance, modern farm inputs, and pest and diseases. To improve the level of yam production and ensure food security in the area, constraints to yam production should be tackled by both public and private sectors by assisting farmers with a wide range of farm input subsidies and affordable credit facilities to invest in yam production for higher productivity, and establishing yam processing industries for value addition.